Prevalence of Campylobacter hepaticus specific antibodies among commercial free-range layers in Australia - Muralidharan, Chithralekha; Huang, Jiongrui; Anwar, Arif; Scott, Peter C.; Moore, Robert J.; Van, Thi Thu Hao (Frontiers in Veterinary Science, 2022)
Spotty Liver Disease (SLD) caused by Campylobacter hepaticus affects the health and productivity of layer hens and is a disease of concern in poultry. In this study, blood and cloacal swab samples were collected from 709 birds across 11 free-range layer farms from different regions of Australia. The prevalence of C. hepaticus specific antibodies and DNA was assessed using a C. hepaticus specific ELISA and PCR and its correlation with mortalities and changes in egg production was analysed to better understand the seroprevalence of C. hepaticus in Australian free-range layer farms. C. hepaticus specific antibodies were detected from birds in four of the five farms that had no history of SLD with seroprevalence as high as 41% in one of the farms. Seroprevalence of anti-C. hepaticus antibodies among flocks that had an active or previous SLD outbreak varied between 2% and 64%. C. hepaticus DNA was detected from birds in three farms with no known SLD history and five farms with confirmed SLD outbreaks. A good correlation was observed between the ELISA and PCR results with a Pearson correlation coefficient value of 0.85 (p-value = 0.001). No correlation was observed between the flock size or flock age and ELISA or PCR outcomes, and no significant difference between the seroprevalence of anti-C. hepaticus antibodies among flocks with or without a known history of SLD was established (p = 0.143). This study demonstrates the usefulness of C. hepaticus specific ELISA and PCR in identifying the occurrence of mild or sub-clinical SLD and provides a broader and more complete understanding of SLD epidemiology that will inform future research aimed at the development of methods to control SLD, such as appropriate biosecurity measures, vaccines, and feed additives.